Variabilitas Multivariat dan Dependensi antar Variabel Penyusun Indeks Pembangunan Manusia di Indonesia - Wilda Riani Hafsah Daulay; Suliadi (Bandung Conference Series: Statistics, 2022)
Abstract. The commonly used multivariate data description measures are Generalized Variance (GV) and correlation coefficient, of that describe the variability and strength of relationship among the variables. However, Generalized Variance is not able to detect changes in the covariance matrix, which shows an increase in variability in some aspects while showing a decrease in variability in other aspects, Meanwhile correlation coefficient can not be used to compare the dependency structure between data sets in data sets with different dimension. In this paper, we will discuss how to apply a good measure of multivariate variability and linear relationships between variables according to Pena & Rodriguez (2003), namely Effective variance and effective dependence. Data used is composing variables of Human Development Index in Indonesia in 2014, 2019 and 2021. It is found that the distribution of variables composing Human Development Index in Indonesia from 2014 to 2019 decreses, so does from 2019 to 2021. Meanwhile, the effective dependence among those variables are weak for all considered years. Abstrak. Ukuran deskripsi data multivariat yang biasa digunakan adalah Generalized Variance (GV) dan koefisien korelasi, yang masing-masing menggambarkan variabilitas dan kekuatan hubungan antar variabel. Akan tetapi Generalized Variance tidak mampu mendeteksi perubahan pada matriks kovarians, yang menunjukkan peningkatan variabilitas dalam beberapa aspek sementara menunjukkan penurunan variabilitas pada aspek lainnya. Sedangkan koefisien korelasi tidak tepat digunakan untuk membandingkan struktur ketergantungan antar kumpulan data pada data set dengan dimensi yang berbeda. Dalam sesi ini akan dibahas bagaimana penerapan ukuran variabilitas multivariat dan hubungan linier antar variabel yang baik menurut Pena & Rodriguez (2003), yaitu Effective variance dan effective dependence. Data yang digunakan adalah data variabel penyusun Indeks Pembangunan Manusia di Indonesia tahun 2014, 2019 dan tahun 2021. Diperoleh bahwa sebaran variabel penyusun Indeks Pembangunan Manusia di Indonesia dari tahun 2014 ke tahun 2019 menurun, demikian juga dari tahun 2019 ke tahun 2021. Sedangkan effective dependence di antara variabel-variabel untuk tahun-tahun tersebut adalah lemah.